The current status of the psychological treatments for bulimia nervosa. - Fairburn, C (1988)
The controlled studies of psychological treatments for bulimia nervosa have yielded findings of practical value. Cognitive behavioural treatments in particular seem promising. However, the bias in research towards the refinement and dismantling of the cognitive behavioural approach is not warranted since certain specific forms of brief psychotherapy have also been shown to benefit these patients. Research into the maintenance of change following pharmacological treatment is needed before drugs can be recommended as an alternative to psychological treatments. The value of combining drugs and psychotherapy is only just beginning to be studied. Regrettably, few treatment studies to date have been designed to further our understanding of the nature of bulimia nervosa.